Identification of two TYRP1 loss‐of‐function alleles in Valais Red sheep. (1st October 2019) - Paris, J. M.; Letko, A.; Häfliger, I. M.; Ammann, P.; Flury, C.; Drögemüller, C.
Summary: The Valais Red sheep breed is a local breed of the Swiss canton Valais. Although the breed is characterised by its brown colour, black animals occasionally occur and the objective of this study was to identify the causative genetic variants responsible for the obvious difference. A GWAS using high‐density SNP data to compare 51 brown and 38 black sheep showed a strong signal on chromosome 2 at the TYRP1 locus. Haplotype analyses revealed three different brown‐associated alleles. The WGS of three sheep revealed four protein‐changing variants within the TYRP1 gene. Three of these variants were associated with the recessively inherited brown coat colour. This includes the known missense variant TYRP1 :c.869G>T designated as b S oay and two novel loss‐of‐function variants. We propose to designate the frame‐shift variant TYRP1 :c.86_87delGA as b VS 1 and the nonsense variant TYRP1 :c.1066C>T as b VS 2 . Interestingly, the b VS 1 allele occurs only in local breeds of Switzerland whereas the b VS 2 allele seems to be more widespread across Europe.